1994
DOI: 10.1016/0168-6496(94)90028-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant DNA transfer to Escherichia coli of human faecal origin in vitro and in digestive tract of gnotobiotic mice

Abstract: The role of helper elements in the mobilisation of pBR recombinant plasmids (tra-, mob-, or/T + and tra-, mob-, or~T-) from genetically engineered Escher/chia coli K12 strains to other K12 strains and to wild-type E. coli strains of human faecal origin was examined. Transfer experiments were done in the digestive tract of axenic (germ free) and gnotobiotic mice, associated with human faecal flora, HFF. The kinetics of implantation of donors, recipients and transconjugants were determined. Mobilisation of or/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Another hypothesis is that E. coli strains (donor and helper) are eliminated too rapidly in the HFF (faster than the transit marker); but despite this rapid transit, the transfer of the helper plasmid pRK2013 was observed. Other studies have demonstrated the same phenomenon [14,18].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Another hypothesis is that E. coli strains (donor and helper) are eliminated too rapidly in the HFF (faster than the transit marker); but despite this rapid transit, the transfer of the helper plasmid pRK2013 was observed. Other studies have demonstrated the same phenomenon [14,18].…”
Section: Discussionsupporting
confidence: 68%
“…We studied the transfer of the pRRI207 from a transconjugant of B. uniformis 1004 (TBUA) to Bacteroides of the HFF. This £ora contained E. coli PG1, which has been demonstrated to promote the transfer of pBR-like recombinant plasmids [18]. After inoculation of TBUA, we observed a considerable modi¢cation among the Bacteroides strains in the micro£ora.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It was found that our experimental conditions led to genetic transfers by conjugation, and mobilization (transfer of plasmid pCE325, in the presence of mob and tra elements). This mobilization had also been demonstrated in the digestive tract of axenic mice at the frequency of lo-" to lo-3 TC/R [31]. The non-detection of plasmid pCE328 transfer by conduction indicates the absence of specific IS sequences that enable the formation of a cointegrate with the conjugative plasmid R388, or else a low transfer frequency precluding the detection of this event in our conditions, Furthermore, these experiments showed the importance of plasmid content in donor bacteria for their establishment in biofilms composed of a recipient strain of E. cd'.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have examined plasmid transfer in laboratory media, and germ free or ex-germ free mice [20,21,23,24] or plasmid transfer under conditions that closely simulate gut environment [25], but the rate of plasmid transfer has not been compared in the different situations. In Schlundt et al [24], the transfer rate varied depending on the donor strain and the recipient strain used and also whether measured in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%